1995
DOI: 10.1017/s1357729800013734
|View full text |Cite
|
Sign up to set email alerts
|

The effect of winter feeding level on subsequent grazing behaviour and herbage intake of Charolais heifers

Abstract: Two groups of eight Charolais heifers were used to examine the effect of feeding level during the post-weaning winter on the grazing behaviour and herbage intake over three periods during the first 2 months of grazing. The winter diets (L and H) were given to achieve a mean difference of 50 kg between groups at turn-out. The heifers were set-stocked together on a hill pasture where sward height was maintained at 12 cm. The -winter live-weight gains were 0-31 and 0-70 (s.e. 0-032) kg/day for L and H heifers res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Biting rate has been found to increase and grazing time to decrease (Hodgson and Jamieson, 1981;Cazcarra and Petit, 1995b) with age and weight of cattle. Other work with Charolais heifers of a similar age found those with a lower live weight grazed longer but tended to have a lower bite rate (Cazcarra and Petit, 1995a). In contrast, during Experiment 1 the older, heavier WB steers spent a higher percentage of time grazing than the CX steers, and as there was no differences in bite rate, there was a corresponding increase in eating prehensions.…”
Section: Grazing Behaviourmentioning
confidence: 68%
See 1 more Smart Citation
“…Biting rate has been found to increase and grazing time to decrease (Hodgson and Jamieson, 1981;Cazcarra and Petit, 1995b) with age and weight of cattle. Other work with Charolais heifers of a similar age found those with a lower live weight grazed longer but tended to have a lower bite rate (Cazcarra and Petit, 1995a). In contrast, during Experiment 1 the older, heavier WB steers spent a higher percentage of time grazing than the CX steers, and as there was no differences in bite rate, there was a corresponding increase in eating prehensions.…”
Section: Grazing Behaviourmentioning
confidence: 68%
“…In contrast, during Experiment 1 the older, heavier WB steers spent a higher percentage of time grazing than the CX steers, and as there was no differences in bite rate, there was a corresponding increase in eating prehensions. This could potentially have led to a higher intake (Cazcarra and Petit, 1995a), which in turn could account for the higher growth rates of the WB steers at this age. However, at 20 months of age the only significant effect of genotype on grazing behaviour was a higher chewing rate for the WB steers, and there was no indication of a potential difference in intake, which is in keeping with the similar growth rates of the two breeds at that time.…”
Section: Grazing Behaviourmentioning
confidence: 99%
“…An alternative approach to managing this type of livestock is to ration cattle to achieve the moderate liveweight gains through the winter in order to exploit compensatory growth in summer (Cazcarra and Petit, 1995). Previous work has demonstrated that compensatory growth can occur in cattle even when herbage allowance or sward height restricts intake (Wright et al, 1986), and a negative association between winterfeeding level and summer liveweight gain has been identified on a range of upland pasture types .…”
Section: Effect On Performance Of Incorporating Grazing Of Semi-naturmentioning
confidence: 99%